The Cape Town church building boom 1880-1909: An Historical and Architectural Review - Martin, Desmond Keith (School of Architecture, Planning and Geomatics, 2020)
This thesis consists of two interrelated parts: a long essay on the building boom, and a catalogue of the churches produced by the boom, or significantly enlarged during the boom. The purpose of the study is two-fold: to provide an analysis of the historical background to the boom and of the architecture of the churches built during the three decades in which it was evident; and to publish a comprehensive catalogue of the churches surveyed, in which both historical and architectural findings for individual church buildings are summarised together with selected photographs, sketches and plans that highlight some of the features of the buildings.This catalogue is intended to provide a ready reference for conservation bodies such as the National Monuments Council and heritage committees